The Future of Privacy in a Connected World: A Socio-Economic Analysis - Judijanto, Loso; Berani, Sogi; Ayaka, Ahmya (Journal of Social Science Utilizing Technology, 2025)
Background. In an increasingly connected world, where data flows seamlessly across digital platforms and devices, the concept of privacy has become more complex and contested. The rise of big data, the Internet of Things (IoT), and artificial intelligence has dramatically altered how personal information is collected, stored, and used. While these technological advancements offer convenience and economic value, they also pose significant risks to individual privacy and raise socio-economic concerns related to surveillance, digital inequality, and data governance. Purpose. This study aims to analyze the future of privacy from a socio-economic perspective by exploring how privacy concerns vary across different income, education, and demographic groups. The research investigates both individual perceptions and institutional practices regarding data protection in the digital age. Method. Using a mixed-methods approach, the study combines a survey of 500 participants from diverse socio-economic backgrounds with in-depth interviews of policymakers, technologists, and privacy advocates. Quantitative data were analyzed using regression models to identify key predictors of privacy concern, while qualitative data were examined thematically to uncover broader social patterns. Results. Findings reveal that lower-income groups often have less access to privacy tools and are more vulnerable to data exploitation. Education level significantly correlates with privacy awareness, and trust in institutions varies widely. The study highlights a growing privacy gap between socio-economic classes, with policy frameworks struggling to keep pace with technological change. Conclusion. The study concludes that equitable privacy protection requires inclusive digital literacy initiatives, transparent regulatory systems, and stronger accountability mechanisms in data-driven environments.